Analysis of Factors Influencing the Intention to Use QRIS As a Payment Tool in Central Kalimantan Province - Mangudu, Mikha; Sfenrianto, Sfenrianto (International Journal of Advances in Data and Information Systems, 2025)
In recent years, the Quick Response Code Indonesian Standard (QRIS) has emerged as a digital payment system in Indonesia. Central Kalimantan has witnessed a substantial increase of 91% in the number of merchants adopting this system in 2021 compared to previous years. However, the significant growth of merchants with QRIS options has not yet had the expected increase in usage frequency. This research aims to identify the factors influencing the utilization of QRIS as a payment method and to formulate recommendations to enhance its adoption. Employing a quantitative method, this study modifies the Technology Acceptance Model (TAM) by including external variables such as Subjective Norm, Perceived Security based on preliminary research to understand their impact on Behavioral Intention to use. Data calculation and analysis were conducted using the SmartPLS 3 tool. The findings reveal that Attitude Toward Using exerts a significant influence on Behavioral Intention to Use. While Subjective Norm, Perceived ease of use and Perceived Usefulness significantly affect usage intention through Attitude Toward Using, this study highlights the potential for increased QRIS adoption by leveraging community figures or influencers in socialization efforts. Furthermore, enhancing perceived usefulness through merchant promotions and user education is crucial for fostering positive attitudes towards QRIS usage.